Fish gelatin and its applications in selected pharmaceutical aspects as alternative source to pork gelatin - Abd Elgadir, Mohammed; Mirghani, Mohamed Elwathig Saeed; Adam, Aishah (WFL Publisher, 2013)
The demand for gelatin for food and pharmaceutical application is increasing because it is one of the most widely used food ingredients. Its applications in food manufacturing are very wide-ranging including enhancing the elasticity, firmness and consistency of food products. Most commercial gelatin is presently sourced from beef bone, hide and pigskin and bones. It was reported that about 41% of the gelatin produced worldwide is basically from pigskin. Fish gelatin represents one of the important types of gelatins from other sources rather than mammalian gelatins and it may thus be considered as an alternative to mammalian gelatin for use in various food and pharmaceutical applications. In the last decades, the rising interest in halal products issues for Muslim populations become one of the main reasons for exploring different types of collagen and gelatin from different animal sources. This review summarizes gelatin in four areas: (1) pig gelatin and halal issue, (3) selected methods used in fish gelatin extraction, (3) selected functional properties of fish gelatin and (4) selected pharmaceutical and medical application of fish gelatin.